Analysis of Organizational Health Index PT. Krakatau Steel, Tbk - Surakusumah, Irma Indriatni; Bangun, Yuni Ros (The Indonesian Journal of Business Administration, 2015)
Abstract.PT. PQR facing several factors that contributes in affected company’s performance such as raw material price, currency exposure, steel demand, regulations, employee’s motivation and capabilities. The external factors affected PT. PQR performance, the company revenue has decrease in the last two years. In fluctuating condition of the company performance, it’s necessary to reviewing the factors that affect the performance of PT. PQR itself.Organizational Health Index (OHI) as a tool to measure the healthiness of the company that has proven linked to company’s performance. McKinsey has proven that the health company has roughly two times greater financial performance from other similar companies. OHI has nine elements that drive company’s performance, Leadership, Direction, Innovation, Culture and Climate, External Orientation, Accountability, Coordination and Control, Motivation and Capability.Leadership influences nine OHI elements and result. Motivation, Coordination and Control, Culture and Climate, Direction and Accountability are the highest elements that affected by Leadership. Accountability, Coordination and Control, Capabilities and Innovation and Learning need Serious improvement in order to improve the company performance.Keywords: Organizational Health Index, Performance, Leadership